Peningkatan Hasil Belajar Matematika dengan Pendekatan Kontekstual pada Materi Pecahan di Kelas 3 MI Nurul Huda - Ningsih Ningsih; Yulina Fadilah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
In this classroom action research carried out to solve problems that occur in the learning process, it is known that the results of learning mathematics in fraction material in grade 3 are not optimal. The purpose of this study was to determine student activity in improving learning outcomes. The research subjects this time were 15 grade 3 MI Nurul Huda students, 7 male students and 8 female students. In this study, it consisted of 2 cycles, namely cycle I and cycle II. The data collection methods used in this study were: observation, interviews, tests and documentation. The results of the research on the activeness of teachers and students have increased, the activeness of teachers in cycle I was 69.23% to 86.83% in cycle II. While the results of student activity also increased in cycle I 65.38% to 88.46% in cycle II. Likewise, student learning outcomes also experienced an increase starting from the pre-cycle with an average acquisition of 65.27% and a completeness percentage of 26.67%, and experienced an increase in the first cycle with an average score of 71.26% and a completeness percentage of 60%. . And in the second cycle research obtained an average of 80.26% and 86.67% completeness percentage. In this way, it can be concluded that using a contextual approach can increase student activity and learning outcomes in learning mathematics in fractional material in class 3 students of MI Nurul Huda.